2003
DOI: 10.1603/0022-2585-40.5.642
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Abundance ofIxodes scapularis(Acari: Ixodidae) and the Tick ParasitoidIxodiphagus hookeri(Hymenoptera: Encyrtidae) with Reduction of White-Tailed Deer

Abstract: The principal vector for the pathogens of Lyme disease, human granulocytic ehrlichiosis, and human babesiosis is the tick Ixodes scapularis Say. A chalcid wasp, Ixodiphagus hookeri, in the family Encyrtidae parasitizes populations of the tick on several islands or other geographically isolated sites in New England with high densities of these ticks and white-tailed deer (Odocoileus virginianus), the principal host for adult I. scapularis. Deer densities were reduced at a forested tract in Bridgeport and the Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 29 publications
6
71
0
Order By: Relevance
“…Similarly, reducing deer density from >90 km −2 to 10 km −2 at Bluff Point coastal reserve in Groton, CT, only reduced tick density below 20 deer per km 2 ( Fig. 2B) (31).…”
Section: Resultsmentioning
confidence: 89%
“…Similarly, reducing deer density from >90 km −2 to 10 km −2 at Bluff Point coastal reserve in Groton, CT, only reduced tick density below 20 deer per km 2 ( Fig. 2B) (31).…”
Section: Resultsmentioning
confidence: 89%
“…Consistent with previous studies (Estrada-Peña, 2001;Lindström and Jaenson, 2003), we found a higher abundance of ticks in oak stands compared to pine stands and a higher tick abundance in fragmented forest sites with a high amount of forest edge habitat, which is most likely related to more optimal environmental conditions and a higher density and activity of the tick's main hosts. Many prior studies have stressed the importance of deer in maintaining tick populations: Gray et al (1992) and Pichon et al (1999) for I. ricinus in Europe and Duffy et al (1994) and Stafford et al (2003) for I. scapularis in the United States. Roe deer are the most common large mammals in the study area and, thus, are probably the most important hosts for adult ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing patch distance is indicative of suburban development, ideal habitat for deer populations. In turn, deer population densities have been shown to be positively associated with tick density (Stafford et al 2003;Wilson et al 1985). On the other hand, white-tailed deer are not competent reservoirs for B. burgdorferi (Telford et al 1988).…”
Section: Discussionmentioning
confidence: 99%